Penerapan Model Pembelajaran Stad Dengan Media Audiovisual untuk Meningkatkan Aktivitas dan Hasil Belajar Materi Perubahan Lingkungan Fisik pada Siswa Kelas IV Sekolah Dasar Negeri 9 Bengkalis Kabupaten Bengkalis - Murti Murti (STAIN Bengkalis, 2017)
The science material environmental changes physical in the fourth grade 9 bengkalis is still dominated by the provision of talk not turn students .The teacher explained and students noted .Teachers also simply contoh-contoh in textbooks , still not use media learning .Students are bored and not watching a lesson .Both teachers and students less active in learning .For that reason , study results obtained too low .This is apparent from the study results students iv in 2014 / 2013 lessons on any material change physical environment there are still many who received scores of students under the criteria at least ( ketuntasan kkm ) .To solve these problems were through the application of stad learning model by the audio visual on any material change of environment physical in the fourth grade 9 bengkalis bengkalis district .The purpose of this research to improve performansi teachers , the activity of student learning and study results science mater. Was used in the study the design of research the act of a class of ( ptk ) that have been carried out in the form of a notebook detailing the development .Per cycle consisting of the meetings of both the through four including planning went through several stages , the implementation of the , observation and reflection .A subject of study this is student of class iv and private primary schools state 9 bengkalis kabupaten bengkalis the new school term of 2013 / 2014 .The technique of collecting data which used is the technique of non-tes and tests from the analysis of qualitative data and quantitative .Indicators of the quality of the success of include the value of the end of performansi teachers would at least be the documents have been obtained the the criteria used to either by the value of letter b ( 71-80 ) , the percentage of liveliness students would at least be the 75 % and value of rata-rata a class of would at least be the reached 60 (kkm installations ipa as well as ) with the percentage of ketuntasan of students to study sekurang- a lack of 75 %. The research results show that the receipt of final score performansi teacher at cycle i is of 87,63 (a ) criteria good.Then increase in cycle ii be 90,99 ( a ) criteria good.The percentage activity learn students on cycle i is 71,60 % then increase in cycle ii be 84,58 %.The performansi teachers and activity student learning to increase their study results students.The average score class obtained at cycle i is 75 with the be completed learning is 75 %.Next been an increase in study results in cycle ii and an average of 82,81 while the be completed learning is 93,75 %.Based on the research done, can be concluded that the implementation of learning model stad with media audio visual on subjects ipa matter environmental changes physical in fourth grade land 9 bengkalis kabupaten bengkalis can increase performansi teachers, student learning activity and the study results.